Brazilian democracy under attack: the populist extreme right, the economic crises and the 2013 protests in Brazil - O. P. Lima Junior; E. R. Hogemann; L. C. S. Lima Dantas (Law and Safety)
The present study aims to understand the role of the economic crises of capitalism, hate speech and populism in the rise of the extreme right in Brazil especially in the 2018 presidential election. For that, a theoretical-descriptive analysis of the causes of these factors was made according to the thesis of historical institutionalism, making use of the hypothetical-deductive method to better understand the crisis of democracy in Brazil and in the world. Finally, an understanding of these peculiar situations is proposed as a pathway to dissolve these tensions so that the population can free itself from these anti-democratic ties and seek the reconstruction of a more participatory, ethical and more democratic Brazil.